Choroidal thickness changes after dynamic exercise as measured by spectral-domain optical coherence tomography - Sayin, Nihat; Kara, Necip; Pekel, Gokhan; Altinkaynak, Hasan (Indian journal of ophthalmology, 2015)
Purpose: To measure the choroidal thickness (CT) after dynamic exercise by using enhanced depth imaging optical coherence tomography (EDI-OCT). Materials and Methods: A total of 19 healthy participants performed 10 min of low-impact, moderate-intensity exercise (i.e., riding a bicycle ergometer) and were examined with EDI-OCT. Each participant was scanned before exercise and afterward at 5 min and 15 min. CT measurement was taken at the fovea and 1000 μ away from the fovea in the nasal, temporal, superior, and inferior regions. Retinal thickness, intraocular pressure, ocular perfusion pressure (OPP), heart rate, and mean blood pressure (mBP) were also measured. Results: A significant increase occurred in OPP and mBP at 5 min and 15 min following exercise (P ˂ 0.05). The mean subfoveal CT at baseline was 344.00 ± 64.71 μm compared to 370.63 ± 66.87 μm at 5 min and 345.31 ± 63.58 μm at 15 min after exercise. CT measurements at all locations significantly increased at 5 min following exercise compared to the baseline (P ˂ 0.001), while measurements at 15 min following exercise did not significant differ compared to the baseline (P ˃ 0.05). There was no significant difference in retinal thickness at any location before and at 5 min and 15 min following exercise (P ˃ 0.05). Conclusion: Findings revealed that dynamic exercise causes a significant increase in CT for at least 5 min following exercise.